Effects of high energy radiation and thermo-chemical environments on polyetherimide composites: futuristic approach to nuclear waste storage. (2017) - Ajeesh, G.; Bhowmik, Shantanu; Sivakumar, Venugopal; Varshney, Lalit; Kumar, Virendra; Abraham, Mathew; Epaarachchi, Jayantha Ananda
This research highlights the effect of radiation, chemical and thermal environments on mechanical and thermal properties of polyetherimide (PEI) composites. The tests are conducted on specimens made from PEI and PEI reinforced with modified Carbon Nano Fibre (CNF). The specimens are subjected to gamma radiation doses of 5 MGy, which is equivalent to the cumulative dose of radiation from spent nuclear fuel until the end of complete radioactivity. The exposed samples are further subjected to highly corrosive and thermal environments. Studies under transmission electron microscopy reveal that there is a uniform dispersion of modified CNF in PEI. Differential Scanning Calorimetry (DSC) and Thermo Gravimetric Analysis (TGA) indicate that there are no significant changes in thermal properties of PEI and PEI composite when exposed to aggressive environments. It is observed that there is a marginal loss in the tensile strength of polymeric samples when exposed to gamma radiation and thermal environments. PEI samples when subjected to alkaline corrosive environments show significant loss in the tensile strength. There is a significant decrease in the molecular weight of PEI under alkaline corrosive environments as seen from Gel Permeable Chromatography (GPC).